KAJIAN KONSEP ARSITEKTUR MODULAR PADA HUNIAN CITÉ A DOCKS STUDENT HOUSING DI LE HAVRE PRANCIS - Shely Pratiwi Sanjaya Putri; Ari Widyati Purwantiasning (Ide dan Dialog Desain Indonesia (Idealog), 2020)
Container is a component that has many sizes and types, in various countries, containers are used as containers to deliver goods. But the last 20 years make containers as a residence is a trend that began to be populer, especially around the port area. The use of containers is one of the right choices because the components are modular and easy to move around, but the construction aspect also needs to be considered in the preparation of those components. The purpose of this research is to understand the concept of modular architecture applied to the occupancy of Cité A Docks Student Housing, either modular system or modular structure using the main components in the form of containers. The research method used in this study is qualitative descriptive with research variables using modular theory from Le Corbusier and prefabricated architectural theory from Ryan E. Smith. The findings of this study obtained that the Cite a Docks building has established the concept of modular architecture, either in the quality of each module of space or on the structure of the building. Each room module size is in accordance with the capacity of each occupant and considers the human scale as the size of each room. In the overall prefabricated structure system already uses steel prefabricated components, but there are different materials on the foundation components, which use reinforced concrete precast materials. Although materially there are 2 types of steel and reinforced concrete, but the entire component of this building has used modular components. Keywords: Vertical Housing, Modular Architecture, Prefabricated Architecture, Containers